UPAYA MENINGKATKAN MOTIVASI BERPRESTASI GURU MELALUI PEMBERIAN REWARD DI SEKOLAH DASAR KECAMATAN KUBU KABUPATEN ROKAN HILIR - Sarmuji Sarmuji (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This study aims to determine whether teacher achievement motivation can be improved through the awarding of awards. This research was conducted at 005 SDN Sungai Sigajah and Tanjung Leban SDN 009 which are contained in a single researcher's supervision. The type of this research is School Action Research. The main reason is from observations and information from the teacher, that teacher teaching motivation is still relatively poor. The sample in this study was all teachers in SD 005 Sungai Sigajah and 007 SDN Tanjung Leban 24 people The results showed that the average score of teacher achievement motivation in the first cycle was 65.33% with the moderate category increasing in the second cycle with an average value of 79.66 which was included in the high category. Indicating that giving rewards has a role in increasing teacher achievement motivation in 005 SDN Sungai Sigajah and SDN 009 Tanjung Leban.